Specifics of arts therapies in educational institutions comparing the institutions of health care setting - Jiri Kantor (Social Welfare: Interdisciplinary Approach)
18 arts therapists from educational and healthcare institutions in Czech Republic were interviewed to determine the specifics of therapeutic practice in educational institutions. The results relate to the presence of different professions in the team, their qualification and  level of therapeutic competence, understanding the roles and work of arts therapists, the impact of arts on institutions, the depth of therapeutic change, formulation of therapeutic contract, therapeutic goals, organisation of therapy, the therapy room and privacy and assessments/evaluation.